THE IMPLEMENTATION OF BLENDED LEARNING IN TEACHING WRITING RECOUNT TEXT FOR EIGHT GRADE STUDENTS (RETAIN, 2016)
THE IMPLEMENTATION OF BLENDED LEARNING IN TEACHING WRITING RECOUNT TEXT FOR EIGHT GRADE STUDENTS Anggraini English Department, Languages and Arts Faculty, The State University of Surabaya Email:anggrainianggraini@mhs.unesa.ac.id Dr. Oikurema Purwati, M.A., M.Appl. English Department, Languages and Arts Faculty, The State University of Surabaya Email: pungki_unesa@yahoo.co.id Abstract This study utilized the qualitative method to explore the implementation of blended learning for teaching secondary school’s English in writing skill. In this study, the researcher observed the implementation of Blended Learning to teach writing recount text, students’ writing skill and also their responses. In this process, rotation model of blended learning is constructed in the teaching and learning process especially in the collecting data stage. In conclusion, Blended Learning can be implemented to teach writing recount text to the eight grade students because it can help them to complete the target of teaching and learning English and get new experience in using online learning contents. Rotation model gave time to students to have cycle through a schedule of independent online study and face to face classroom time. Keywords:Blended Learning, Writing, Recount Text Abstrak Penelitian ini menggunakan metode kualitatif untuk mengetahui implementasi Blended Learning recount untuk siswa kelas delapan. Penulis mengamati implementasi, hasil menulis siswa, danjugaresponmereka. Pada proses ini, model rotasi dari Blended Learning dipergunakan dalam proses pengajaran, lebih tepatnya pada bagian mengumpulkan data. Pada kesimpulannya, Blended Learning dapati implementasikan pada pengajaran menulis teks recount untuk siswa kelas delapan karena dapat membantu mereka mencapai target dan memberikan pengalaman baru dalam penggunaan konten online. Model rotasi memberikan mereka waktu untuk berkesempatan belajar secara sendiri dengan konten online dan juga tatap muka langsung. Kata Kunci: Blended Learning, Menulis, Teks Recount